A comparative study on protein separation using different techniques - Jamilah, Junuh (2009)
Concentration of commercial soy milk into protein stream using crossflow filtration unit with ultrafiltration membrane and conventional method was examined. Two membranes of molecular weight cut off (MWCO) of 10 and 50 kilo Dalton (kDa) of regenerated polysulfone material were used to determine the better techniques and efficiency of the process. The performance was determined under various processing conditions that include the operating transmembrane pressure the pore size of the membrane. Partially soymilk was centrifugated at 8000 rpm and 30 minutes in 20oC to remove the colloidal materials to prevent the membrane fouling. It is found that the permeate flux for 10kDa membrane are decreased with time. This is due to fouling of the membrane. An increased in transmembrane pressure increased the permeate flux and protein weight. The 10kDa membrane shows that the ability to adsorb more amount protein instead of 50kDa membrane. The weight of protein being low at lower transmembrane pressure (less than 10psig) and high at higher transmembrane pressures (greater than 15 psig). The amount of protein recovered at greater transmembrane pressure is more than 5 grams. The method of isolation (conventional method) were adjusted the pH of soy milk (dilute with distilled water) to 4.6 at 20oC. Used this method gives a weight of protein in not more than 5 grams. It is found that the best membrane to retain highest weight of protein is 10kDa.